2018
DOI: 10.3389/fpsyg.2018.01488
|View full text |Cite
|
Sign up to set email alerts
|

Music Preferences and Personality in Brazilians

Abstract: This article analyzes the relationship between musical preference and type of personality in a large group of Brazilian young and adult participants (N = 1050). The study included 25 of 27 states of Brazil and individuals aged between 16 and 71 years (M = 30.87; SD = 10.50). Of these, 500 were male (47.6%) and 550 were female (52.4%). A correlational study was carried out applying two online questionnaires with quality parameters (content-construct validity and reliability), one on musical preference and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
6
24
2
2
Order By: Relevance
“…The fourth dimension, Contemporary, comprised rhythmic and percussive styles connected to issues of social justice and opportunities for lower SES populations, which converged with the findings of several authors [6,15,16,32]. Lastly, the fifth dimension, Mellow, comprised relaxing musical styles with smooth rhythms and sentimental vocals, consistent with the dimensions Upbeat and Conventional found by prior studies [7,10,48], as well as with dimension Upbeat found by Herrera et al [17]. Despite the variability in dimension composition, we argue that the results of this study confirm the five-factor structure of musical preferences proposed by Rentfrow et al [11].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The fourth dimension, Contemporary, comprised rhythmic and percussive styles connected to issues of social justice and opportunities for lower SES populations, which converged with the findings of several authors [6,15,16,32]. Lastly, the fifth dimension, Mellow, comprised relaxing musical styles with smooth rhythms and sentimental vocals, consistent with the dimensions Upbeat and Conventional found by prior studies [7,10,48], as well as with dimension Upbeat found by Herrera et al [17]. Despite the variability in dimension composition, we argue that the results of this study confirm the five-factor structure of musical preferences proposed by Rentfrow et al [11].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, it is worth noticing that most of the music styles comprising this dimension are originally from Brazil and connected to dance. These are similar to Música de Massa dimension by Gouveia et al [8], and Brazilian Mainstream Music dimension by Herrera et al [17]. The third dimension, Sophisticated, consisted of music styles perceived as complex, intelligent, and inspiring, which related to findings from other studies [9,16,47].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Within the models of personality, the Five Factor Model (McCrae and Costa, 1997) has been the most developed (Herrera et al, 2018), and it represents the dominant conceptualization of the structure of personality in current literature. It postulates that the five great factors of personality (emotional instability, extraversion, intellect/imagination, agreeableness, and conscientiousness) are found at the highest level in the hierarchy of personality.…”
Section: Personalitymentioning
confidence: 99%